Analysis of Public Information Disclosure: A Study on Improving Competency Development Training at the Bukittinggi Regional Human Resources Development Center of the Ministry of Home Affairs - Edward, Aurelia Valentin; Putri, Nora Eka; Magriasti, Lince; Nora, Desri (SAFE-Network, 2025)
This study analyzes the implementation of public information disclosure in supporting competency development training for civil servants at PPSDM Regional Bukittinggi, Ministry of Home Affairs. Using a descriptive qualitative approach with a case study method, data were collected through in depth interviews, observations, and document analysis involving structural officials, information management staff, and targeted civil servant participants. The findings reveal that the current dissemination of training information remains suboptimal, relying primarily on manual correspondence through BKPSDM offices. This approach results in slow delivery, limited reach, and unequal access among civil servants, compounded by the underutilization of digital platforms, absence of structured communication policies, and lack of dedicated public relations resources. However, existing regulatory support, the growing need for competency development, and the availability of digital infrastructure present significant opportunities for improvement. The study recommends the development of an integrated web-based information system, active use of social media for interactive engagement, and the institutionalization of public relations functions. These strategies are expected to enhance accessibility, participation, and public trust while serving as a replicable model for other multi regional training centers. The findings underscore the importance of shifting toward proactive, technology driven, and resource supported public information management to strengthen transparency and efficiency in civil servant competency development.